Business Administration and Business Economics: Array - Collective Authors (Acta Universitatis Danubius. Œconomica, 2021)
The study employed co-integration analysis to identify factors that influence company tax revenue collections in Swaziland and further uses ARIMA and VAR to find a forecasting technique that will produce the least forecasting variance for CIT revenue. The results reveal that GDP, Share of Agriculture in GDP and Tax Rate have a positive and statistically significant relationship with company tax revenue while inflation and openness showed a negative and statistically significant relationship. These findings are mostly consistent with theoretical expectations and other studies that were done by other researchers. Combined forecasting was found to produce the least variance for one year ahead forecast of company tax revenue.